An Addition to the Study of Crime of Isija Feratagić - Zarković, Vesna (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
This paper discusses the crimes against the Serbs of Mitrovica and the surrounding area, committed by the Albanian criminals, among whom Isija Feratagić stood out. His atrocities significantly affected the position of the Serbian population and often led them to leave their households and emigrate to the Kingdom of Serbia. Turkish authorities were often uninterested in preventing the Albanians incidents, and military interventions mostly escalated into a conflict between the army and the Albanians. Such a situation had a negative impact on the lives of Serbs, not only in Mitrovica and its surroundings, but also in the entire province of Kosovo. The Serbian people in Old Serbia, with the support of the Government from Belgrade and the representatives of Russia, sent complaints to the Turkish authorities and the Sultan in Constantinople countless times, as well as to the representatives of the great powers. Under their influence, the Porte was forced to accept the implementation of reforms. Isija Feratagić, who in his actions was guided by personal interests and the lowest impulses, was pushed into the background and is no longer found in the reports of the consuls.